A cross-sectional study on stress perceived by families of mentally retarded children enrolled in special schools of a city of central India - Chourasiya, Sanjay Kumar; Baghel, Anil; Kale, Saket; Verma, Arpit (International Journal Of Community Medicine And Public Health, 2018)
Background: Presently we are passing through a phase in the area of rehabilitation where in efforts are being made to spread services and training programs to raise awareness level related to mainstreaming and provision of equal rights and opportunity for the mentally retarded individuals. The present study was undertaken keeping in view the fact that an increasing number of children are being diagnosed with mental retardation parallelly an increase number of families will have to address and cope with the stress. The objective of the study was to study the stress perceived by the families having mentally retarded children and to find out the various factors influencing the perceived stress Methods: 100 families and102 mentally retarded children were studied. Section I of family interview for stress and coping in mental retardation (FISC-MR) was used to find out the family burden of care. Results: 47.97% of fathers and 68% of mothers are in the age group of 30-40 years. The severity of retardation was mild in 36 children, moderate in 46 children while 20 had severe retardation, 32% of mother feel mild stress of which 59.3% having education level up to degree college. 61% of mother showing moderate stress of which 68.8% having education level up to degree college. (67.3%) nuclear families show mild stress while only 22 (52.3%) joint families show mild stress. Conclusions: Living with and caring for the person with MR is very stressful and burdensome. High level of stress and burden is associated with increased level of disability; it being the maximum in the caregivers of persons with severe to profound Mental Retardation.